Effect of ultraviolet light on mood, depressive disorders and well‐being. Issue 5 (25th June 2018) - Veleva, Bistra I.; van Bezooijen, Rutger L.; Chel, Victor G. M.; Numans, Mattijs E.; Caljouw, Monique A. A.
Summary: Background: Human and animal studies have shown that exposure to ultraviolet light can incite a chain of endocrine, immunologic, and neurohumoral reactions that might affect mood. This review focuses on the evidence from clinical trials and observational studies on the effect of ultraviolet light on mood, depressive disorders, and well‐being. Methods: A search was made in PubMed, Embase, Web of Science, Cochrane, Psychinfo, CINAHL, Academic Search Premier and Science Direct, and the references of key papers, for clinical trials and observational studies describing the effect of ultraviolet light applied to skin or eyes on mood, depressive disorders, and well‐being. Results: Of the seven studies eligible for this review, the effect of ultraviolet light on mood, depressive symptoms and seasonal affective disorders was positive in six of them. Conclusions: Of the seven studies, six demonstrated benefit of exposure to ultraviolet radiation and improvement in mood which supports a positive effect of ultraviolet light on mood. Because of the small number of the studies and their heterogeneity, more research is warranted to confirm and document this correlation.